Pyrite nanotube array films as an efficient photocatalyst for degradation of methylene blue and phenol1. Issue 77 (22nd August 2015) - Tian, Ang; Xu, Quan; Shi, Xiaoguo; Yang, He; Xue, Xiangxin; You, Junhua; Wang, Xiaoqiang; Dong, Chenbo; Yan, Xin; Zhou, Hongjun
<x xml:space="preserve">Abstract</x> The nanotube topography would improve the optical property of the pyrite crystals. The photodegradation of MB and phenol suggested that the pyrite nanotubes array films would be potential to be used in the treatment of pollutants.